The Relationships Between the Impact of Alcoholic Beverage Control Policies, Selected Contextual Determinants, and Alcohol Drinking in Spain. (15th October 2014) - Matrai, Silvia; Casajuana, Cristina; Allamani, Allaman; Baccini, Michela; Pepe, Pasquale; Massini, Giulia; Gual, Antoni
Abstract : Alcohol prevention policies alone neither cause nor explain changes in alcohol consumption, nor in related harm. Alcohol consumption in Spain throughout the period 1962–2008 was analyzed considering selected contextual factors and alcohol policies. Increased urbanization was found to be associated with higher consumption, especially of beer. Restrictive policies regulating purchase age, advertising, and licensing premises to sell alcohol were associated with decreased alcohol consumption, while lower blood alcohol concentration limits were followed by an increase. Study limitations are noted. Changes in the evolution of socioeconomic, sociodemographic, and cultural factors should be carefully analyzed to inform alcohol policy planning and evaluation.